Neuroéducation et pédagogie - Sylvain Connac (Éducation et Socialisation)
There are several research studies in neuroeducation and they are directly linked to the teachers activity because they aim at an in-depth understanding of the brain mechanisms in terms of cognition. Research studies in pedagogy are part of the educational challenge which consists in encouraging achievements for each pupil. This paper offers a schematic formalization of the learning act, closest to current neuroeducation works, to try to take part in the improvement of the links between teaching and learning. It shows, on the one hand, cognitive activities concerning the process of the learning act (attentiveness, understanding, memorization and transfer) and, on the other hand, families of conditions which would facilitate the development of this process (in terms of safety, availability and involvement).